Endocrine disruption in aquatic pulmonate molluscs few evidences, many challenges - Lagadic, Laurent (Ecotoxicology (London, England), 2007)
As compared to other groups of aquatic gastropods, documented examples of endocrine disruption in pulmonates are rather limited. This is quite surprising because the endocrine control of physiological functions has been extensively studied in these animals. In the model-species Lymnaea stagnalis, the neurohormonal regulation of reproduction has been thoroughly investigated, and the primary structure of several peptides and receptors involved in endocrine processes has been established. However, the use of this knowledge has been fairly limited in the context of ecotoxicology, to investigate the effects of endocrine-disrupting chemicals. The present review summarizes the main and more recent findings on the neuroendocrine control of reproduction in aquatic pulmonate snails (Basommatophora). It then comprehensively describes selected in vivo laboratory and semi-field studies which provide evidence for possible endocrine disrupting effects of estrogenic and androgenic test compounds [e.g., ethynylestradiol, methyltestosterone (MT)], and of environmental contaminants [e.g., cadmium (Cd), tributyltin (TBT), and nonylphenol (NP), pesticides]. Finally, challenging perspectives for future research are discussed